Pengaruh Pendudukan Jepang terhadap Perkembangan Militer Sumatera Selatan Tahun 1942-1947 - Lailatul Munawaroh; Ira Miyarni Sustianingsih; Sarkowi Sarkowi (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
This study aims to describe the influence of the Japanese occupation on military developments in South Sumatra in 1942-1947. The method used in this research is historical research (historical). The steps used include: Heuristics, Source Criticism, Interpretation, and Historiography. The results showed that during the Japanese occupation of Indonesia, South Sumatra was used as a core area by the Japanese in the economic field. In addition, the youths were made as volunteer soldiers (Gyugun) by the Japanese who aimed to assist the Japanese army in defending the occupied area from Allied counterattacks. After the Japanese occupation ended and left South Sumatra, the former volunteer soldiers (Gyugun) who had been formed by the Japanese occupied important positions during the struggle for independence, which later became the pioneers of the establishment of BKR/TKR in South Sumatra. The conclusion of this study is that Japan formed a Gyugun training center, by providing doctrine and training with a Japanese military model that was both physically and mentally tough in order to become a Bushido soldier to help fight Japan against its allies. Keywords: Influence, Japanese Occupation, Military.